Implementation of Regional Regulation Number 3 of 2017 on Smoke-Free Areas and Its Relation to Law Number 22 of 2009 on Road Traffic and Transportation in the Regulation of Smoking on Public Roads - Maryani, Maryani; Habbibi, Habbibi; Sahroni, Iron; Hardiyanto, Hardiyanto; Indra, Andi Rachmat; Apridon, Pri (International Journal of Business, Law, and Education, 2025)
Smoking behavior on public roads poses a dual threat to public health and traffic safety. This study examines the juridical relationship between the implementation of Regional Regulation Number 3 of 2017 on Smoke-Free Areas (Kawasan Tanpa Rokok) and Law Number 22 of 2009 on Road Traffic and Transportation concerning the regulation of smoking behavior on public roads. Using a juridical-normative approach with qualitative descriptive analysis, this study explores the harmony and challenges of both legal instruments in protecting the public from smoking-related risks. The findings indicate that both regulations share the same preventive objective—protecting the public from the negative effects of smoking and reducing traffic risks caused by driver distraction. However, implementation remains weak due to low public awareness, insufficient coordination between law enforcement agencies, and limited supervision. The study concludes that the effectiveness of these regulations depends on strengthening inter-institutional collaboration, integrating enforcement mechanisms, and enhancing public education to foster compliance. The synchronization of health and transportation law enforcement is essential to realize safer and healthier public spaces.